Penghinaan terhadap Rasulullah s.a.w. : implikasi hukum, menelusuri sejarah, dan isu kontemporari : kami membela mu wahai Rasulullah - Riduan Mohamad Nor.; Mohd. Asri Mat Daud. (Batu Caves, Selangor Darul Ehsan : MHI Publication, 2006)
Blasphemy of Islam and the Prophet by western newspapers and what Muslims in Malaysia should do against it.
Includes bibliographical references (p. 99-100).
In Malay.
Keywords: Blasphemy (Islam); Libel and slander -- Religious aspects -- Islam; Islam in mass media; Religious awakening -- Islam; Public opinion -- Malaysia